Curriculum windows : what curriculum theorists from the 1950s can teach us about schools and society today - Poetter, Thomas S. (Thomas Stewart), 1962- (Charlotte, NC : Information Age Publishing, Inc., 2019)
"Curriculum Windows: What Curriculum Theorists of the 1950s Can Teach Us about Schools and Society Today is an effort by students of curriculum studies, along with their professor, to interpret and understand curriculum texts and theorists of the 1950s in contemporary terms. The authors explore how key books/authors from the curriculum field of the 1950s illuminate new possibilities forward for us as scholar educators today: How might the theories, practices, and ideas wrapped up in curriculum texts of the 1950s still resonate with us, allow us to see backward in time and forward in time - all at the same time? How might these figurative windows of insight, thought, ideas, fantasy, and fancy make us think differently about curriculum, teaching, learning, students, education, leadership, and schools? Further, how might they help us see more clearly, even perhaps put us on a path to correct the mistakes and missteps of intervening decades and of today? The chapter authors and editor revisit and interpret several of the most important works in the curriculum field of the 1950s. The book's Foreword is by renowned curriculum theorist William H. Schubert"--
Foreword: Curriculum windows : the 1950s -- Preface: 1950s volume -- Introduction: Curriculum windows of the 1950s -- Calling a truce : Rudolf Flesch and the reading war / Esther Claros-Berlioz -- There were bugs in the window / Adam H. Frank -- We will not teach in fear : reclaiming our voice in the complicated conversation / M.A. Moyer -- Creativity and the windowless classroom / Don C. Murray -- A personal exploration of my journey from nongraded to graded / Serian Jeng -- Bloom's taxonomy : six decades of the cognitive domain / John Chambers -- Looking in the residence hall window to the future / Colleen E. Bunn -- Creating the world outside your window / Daniel L. Coleman -- 2016 : the new 1957 / Robyn Jordan -- The Tyler rationale : a model of curriculum architecture / Vijay Keshaorao Paralkar -- Florence Stratemeyer : a visionary forgotten / Kevin Fitzgerald -- Tea with Taba / Peggy Larrick.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Education -- Curricula -- United States -- History -- 20th century; Curriculum planning -- United States -- History -- 20th century; Education -- Social aspects -- United States -- History -- 20th century; Nineteen fifties; Programmes d'études -- États-Unis -- Histoire -- 20e siècle.; Années cinquante (Vingtième siècle); Curriculum planning; Education -- Curricula; Education -- Social aspects; Nineteen fifties; United States; 1900-1999; History